Pengaruh Struktur Organisasi terhadap Perilaku Warga Sekolah Menengah Atas - Astuti, Devi; Hendriani, Suswati (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This study aims to examine the impact of organizational structure on the behavior of the members of SMAN 1 Sawahlunto. Utilizing qualitative methods, this research involved direct observation and in-depth interviews with various stakeholders at the school, including the principal, teachers, students, and administrative staff. The results indicate that SMAN 1 Sawahlunto implements a hierarchical organizational structure, with the principal at the top, followed by vice principals, department heads, teachers, and administrative staff. This structure has several significant impacts on the behavior of the school community. Firstly, teachers tend to follow instructions from superiors without much debate, which can reduce their personal initiative and creativity in teaching. Secondly, students have a high level of respect for teachers and administrative staff, creating a disciplined environment, but they sometimes feel less confident in expressing their opinions or new ideas, which can limit active participation and the development of critical skills. Thirdly, the administrative staff strictly follows established procedures, ensuring efficiency and consistency in routine tasks, but they are less flexible in dealing with unexpected situations. In conclusion, the hierarchical structure at SMAN 1 Sawahlunto creates an orderly and disciplined environment, but it also presents challenges in terms of flexibility, initiative, and active participation. It is recommended that the school consider adopting a more participative and flexible approach to optimize the potential of all its members.